Intermediate Syndrome in Organo Phosphorous Poisoning Patients admitted to ICU-A Retrospective Analysis - Neha Nupoor; Suresh Kumar Nagaiah; Ravi Madhusudhana; Anusha Raj; Dinesh Krish-namurthy; Prabhakar Kamarthi (Journal of Clinical and Biomedical Sciences)
Background: Poisoning with Organophosphorus (OP) compounds is one of the most common presentations we come across in critical care units. Recognition and initiation of immediate treatment holds key to the outcome. Aims: To study the outcome of OP compound poisoning patients, the effect of delay and the frequency of Intermediate syndrome. The case sheets of patients admitted with OP compound poisoning to ICU in medical college referral hospital were retrospectively analysed. Materials and methods: We have done retrospective analysis of 177 patients admitted to the emergency department with history of acute OP poisoning. Eight patients were brought dead, 10 patients were referred and 159 patients were admitted to ICU. Statistical analysis: Student t- test is used to find the significance of study parameters on continuous scale between two groups on metric parameters. Chi-square/ Fisher Exact test is used to find the signifi-cance of study parameters on categorical scale between two or more groups. Results: We found that Inter-mediate syndrome is commonly seen when there is delay of more than 9 hours for hospitalization following OP compound consumption and delay in starting atropine and PAM. Conclusions: OP composed insecticide poisoning is a life threatening condition that needs rapid diagnosis and treatment with good supportive care, starting of early enteral feeds, monitoring for the prevention and management of acute and delayed complications that occur during the course of stay in ICU. Keywords: Intermediate syndrome, OP poisoning, ICU, Retrospective analysis.